Upaya Meningkatkan Hasil Belajar IPS Materi Ekonomi Kreatif Melalui Model Project Based Learning Pada Siswa Kelas IX D Siswa SMP Negeri 1 Salam Semester 2 Tahun Pelajaran 2021/2022 - Kingkin Pinandoyo, Sukorini (Science and Education Journal (SICEDU), 2022)
Problems in learning Social is a lot of memorizing to many material, the passive students, low activities, that they are only as listener and shy for asking. To overcome this problem, aclass action research (PTK) was conducted using Project based learning model. The purpose of this study was to improve the learning outcomes of IX D grade studentsof SMP Negeri 1 Salam school year 2021/2022 using the Project based learning model. The research subjects were students totaling 31 people, the sourceof research data obtained from qualitative data in the form of data observation activities of teachers and students and quantitative data in the form of student learning outcomes test data. The results of the first cycle of research obtained by students who completed individually as many as 26 students with classical completeness of 84%. While the results of these condcycle of research has increased with the number of students who completed individually as many as 31 students with a percentage of completeness of 100 %. Based on the results of the study, learning using the Project based learning model can improve the learning outcomes of IX D grade students of SMP Negeri1 Salam school year 2021/2022.